Does an increase in adipose tissue ‘weight’ affect male fertility? A systematic review and meta‐analysis based on semen analysis performed using the WHO 2010 criteria - Santi, Daniele; Lotti, Francesco; Sparano, Clotilde; Rastrelli, Giulia; Isidori, Andrea M.; Pivonello, Rosario; Barbonetti, Arcangelo; Salonia, Andrea; Minhas, Suks; Krausz, Csilla; Vignozzi, Linda; Maggi, Mario; et al. (Andrology (Oxford), 2024)
Introduction Obesity negatively impact on the metabolism of sex hormones, leading to reduced testosterone serum levels. However, how the obesity could negatively impact on the overall gonadal function, particularly on male fertility, remained unclear so far. Objective To systematically review evidences regarding the influence of body weight excess on the sperm production. Methods A meta‐analysis was conducted, searching all prospective and retrospective observational studies reporting male subjects older than 18 years old, with body weight excess from overweight to severe obesity were considered. Only studies using the V edition of the World Health Organization (WHO) manual for semen analysis interpretation were considered. No specific interventions were considered. Search was focused on studies comparing overweight/obese to normal weight subjects. Results Twenty‐eight studies were considered. Total sperm count and sperm progressive motility were significantly lower in overweight compared to normal weight subjects. Meta‐regression analyses demonstrated that patients’ age impacted on sperm parameters. Similarly, obese men showed lower sperm concentration, total sperm number, progressive and total motilities, and normal morphology lower than normal weight subjects. Reduced sperm concentration in obese men was influenced by age, smoking habit, varicocele, and total testosterone serum levels at meta‐regression analyses. Conclusions The male potential fertility is reduced in subjects with increased body weight, compared to normal weight men. The higher was the increased body weight, the worst was the sperm quantity/quality. This result comprehensively included obesity among non‐communicable risk factor for male infertility, shedding new lights on the negative impact of increased body weight on overall gonadal function.